Implementation Of The Principle Of Good Governance Responsibility In Improving Public Services At The Office Of The Lurah Of Simardan Island - Sila Insan Tikayani; Irawan Irawan; Ayu Kurnia Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
One of the main benchmarks for the successful implementation of good governance principles at the local level is the availability of responsive public services. This study aims to apply the principle of responsibility to improve public services at the Simardan Island Village Office, Tanjung Balai City. The method used is a descriptive qualitative approach, with data collection through in-depth interviews, field observations, and documentation studies. The research informants included the village head, service staff, the community, and residents who received services. The research findings revealed that the implementation of the principle of responsiveness at the Simardan Island Village Office has been implemented, but has not reached an optimal level, as evidenced by the ongoing complaint handling, limited human resources, and the unavailability of a digital technology- based complaint system. Factors supporting the implementation of responsibility include commitment from leaders and a good attitude of cooperation from staff, while inhibiting factors include limited facilities and infrastructure and low community participation. This study concludes that improving staff capabilities and the use of information technology are important strategic steps to improve public service accountability at the village level.